Contribution of Environment Sample-Based Detection to Ebola Outbreak Management. (16th October 2018) - Kapetshi, Jimmy; Fausther-Bovendo, Hugues; Corbett, Cindi; Leung, Anders; Ait-Ikhlef, Kamal; Nsio, Justus; Aruna, Aaron; Kebela Ilunga, Benoit; Muyembe, Jean-Jacques; Formenty, Pierre; Kobinger, Gary P
Abstract: Detection of chains of transmission is critical to interrupt Ebola virus (EBOV) outbreaks. For >25 years, quantitative reverse transcription polymerase chain reaction performed on biological fluids has been the reference standard for EBOV detection and identification. In the current study, we investigated the use of environmental sampling to detect EBOV shed from probable case patients buried without the collection of bodily fluids. During the 2012 Bundibugyo virus (BDBV) outbreak in the Democratic Republic of the Congo, environmental samples were screened for BDBV RNA by means of real-time polymerase chain reaction. Low levels of BDBV genomic RNA were detected in a hospital and in a house. Detection of BDBV RNA in the house led to the identification of the last chain of transmission still active, which resulted in the safe burial of the person with the last laboratory-confirmed case of this outbreak. Overall, environmental sampling can fill specific gaps to help confirm EBOV positivity and therefore be of value in outbreak management.